2017
DOI: 10.1007/s13311-016-0485-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide and Curcumin Co-Stimulation Potentiates Olfactory Ensheathing Cell Phagocytosis Via Enhancing Their Activation

Abstract: The gradual deterioration following central nervous system (CNS) injuries or neurodegenerative disorders is usually accompanied by infiltration of degenerated and apoptotic neural tissue debris. A rapid and efficient clearance of these deteriorated cell products is of pivotal importance in creating a permissive environment for regeneration of those damaged neurons. Our recent report revealed that the phagocytic activity of olfactory ensheathing cells (OECs) can make a substantial contribution to neuronal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 75 publications
2
45
0
Order By: Relevance
“…Olfactory neurons undergo cell death via apoptosis upon reaching the end of their lifespan, displaying the "eat me" signal phosphatidylserine. In vitro studies have shown that OECs recognize phosphatidylserine on apoptotic neurons via phosphatidylserine receptors prior to engulfment (He et al, 2014;Hao et al, 2017). As discussed earlier, phagocytes usually possess a number of receptors that recognize phosphatidylserine on an apoptotic target; while some receptors directly recognize phosphatidylserine, others require bridging molecules to aid attachment.…”
Section: Oec Phagocytosis In Normal Physiological Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Olfactory neurons undergo cell death via apoptosis upon reaching the end of their lifespan, displaying the "eat me" signal phosphatidylserine. In vitro studies have shown that OECs recognize phosphatidylserine on apoptotic neurons via phosphatidylserine receptors prior to engulfment (He et al, 2014;Hao et al, 2017). As discussed earlier, phagocytes usually possess a number of receptors that recognize phosphatidylserine on an apoptotic target; while some receptors directly recognize phosphatidylserine, others require bridging molecules to aid attachment.…”
Section: Oec Phagocytosis In Normal Physiological Conditionsmentioning
confidence: 99%
“…In vitro phagocytic assays have also shown that OECs are capable of taking up debris derived from several types of axons (generated by destruction of axons, thus resembling an injury containing both apoptotic and necrotic bodies) as well as myelin debris (He et al, 2014;Nazareth et al, 2015aNazareth et al, , 2020Khankan et al, 2016;Hao et al, 2017). OECs can, like SCs, actively phagocytose and degrade necrotic cells in vitro (also via phosphatidylserine recognition).…”
Section: Olfactory Nerve Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…The transplanted cells are thought to promote regeneration by secreting growth factors and guidance factors, by providing physical support, and by clearing debris arising from dead cells 13,15 . It has also been suggested that stimulation of the phagocytic activity to more rapidly clear the injury site of cell debris will further promote regeneration 13,[17][18][19][20][21] . To date, it remains unknown how peripheral glia recognize, internalize and process necrotic targets.…”
mentioning
confidence: 99%
“…As debris removal is critical for regeneration, stimulation of OEC phagocytosis may also be favourable. Low-dose curcumin has been shown to strongly stimulate the phagocytic activity of OECs 13,27 , in addition to stimulating both proliferation and migration 13 . Eremophila microtheca compounds have also been shown to enhance phagocytic activity, migration and cell viability of OECs 15 .…”
mentioning
confidence: 99%